Effects of wheat germ diet on intestinal antioxidant capacity, immunological function and gut microbiota of Sichuan white geese - Wang, Xin; Jiang, Dongmei; An, Xiaoguang; Li, Shuo; Qi, Yuxin; Yang, Yujie; Wang, Zelong; Sun, Qian; Ling, Weikang; Ji, Chengweng; Qi, Yuxuan; Xu, Hengyong; et al. (Frontiers in Microbiology, 2024)
Background Wheat germ is known for its antioxidant, anti-inflammatory, and disease resistance properties in animals. However, its effect on the gut of Sichuan white geese remains unclear. Method In this study, thirty 250-day-old geese were divided into three equal groups, the control group, LWG group (21.8% wheat germ) and HWG group (43.6% wheat germ), the experiment lasted 12 weeks. We assessed various aspects of geese intestinal health, including barrier function, digestibility, antioxidant capacity, immunity, microbiota, and metabolism. Results The study revealed a significant increase in villus height (VH), villus height-to-crypt depth (VH/CD) ratio, amylase, and lipase activities in the duodenum and ileum, increased putrescine levels in the duodenum and jejunum, as well as spermidine levels in the jejunum(P < 0.05). LWG increased the total antioxidant capacity (T-AOC) in the duodenum, while decreasing levels of intestinal malondialdehyde (MDA), serum lipopolysaccharide (LPS), interleukin-6 (IL-6), and diamine oxidase (DAO) activity (P < 0.05). Furthermore, LWG increased the relative abundance of Oscillospiraceae_unclassified, Ligilactobacillus, and Roseburia, as well as increased levels of acetic acid, butyric acid, and valeric acid, while decreasing the relative abundance of Subdoligranulum, Flavonifractor, and Klebsiella. Additionally, we observed 17 up-regulated genes and 25 down-regulated genes in the jejunum, which are associated with the cell cycle and immunity. These genes play roles in pathways such as the p53 signaling pathway, cell cycle regulation, and pathways associated with immune modulation. On the other hand, HWG increased intestinal VH and spermidine content, as well as amylase and lipase activities in the duodenum (P < 0.05). It also elevated ileal T-AOC and sIgA levels ( P <0.05), while reducing intestinal MDA content, serum LPS levels, DAO activity, and propionic acid in cecum contents (P < 0.05). Moreover, HWG increased the relative abundance of Ligilactobacillus, Oscillospiraceae_unclassified, and Roseburia (P < 0.05). Conclusion Overall, wheat germ diets, particularly the LWG diet demonstrated the ability to enhance antioxidant capacity, digestibility, immunity, and barrier properties of the intestinal tract, while modulating the gut microbiota and metabolism. Therefore, wheat germ diets hold promise in improving intestinal health by preserving barrier function and regulating flora structure.